2020
DOI: 10.1093/cid/ciaa420
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology of Mycobacterium tuberculosis To Describe the Transmission Dynamics Among Inuit Residing in Iqaluit Nunavut Using Whole-Genome Sequencing

Abstract: Background In the last decade, tuberculosis (TB) incidence among Inuit in the Canadian Arctic has been rising. Our aim was to better understand the transmission dynamics of TB in this remote region of Canada using whole-genome sequencing. Methods Isolates from patients who had culture-positive pulmonary TB in Iqaluit, Nunavut, between 2009 and 2015 underwent whole-genome sequencing (WGS). The number of transmission events bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…(38, 39) One study found a homeless shelter and a gambling house hosted super-spreading events in Nunavut and suggested the important roles socioeconomic factors play in the transmission of TB. (42) Nunavik, an Inuit region in Northern Quebec, had a TB incidence rate of 199.5/100,000. (40) In 2021, TB among Inuit (170/100,000) was 300 times more prevalent compared to non-Indigenous populations (0.5/100,000).…”
Section: Bmi: Body Massmentioning
confidence: 99%
“…(38, 39) One study found a homeless shelter and a gambling house hosted super-spreading events in Nunavut and suggested the important roles socioeconomic factors play in the transmission of TB. (42) Nunavik, an Inuit region in Northern Quebec, had a TB incidence rate of 199.5/100,000. (40) In 2021, TB among Inuit (170/100,000) was 300 times more prevalent compared to non-Indigenous populations (0.5/100,000).…”
Section: Bmi: Body Massmentioning
confidence: 99%
“…The Health Canada Strategy, based on high-quality tuberculosis programming at the community and regional levels, echoes the Canadian Tuberculosis Standard defined tuberculosis control activities, such as early case finding, contact identification, and surveillance (data collection, analysis, and dissemination) [ 2 , 7 , 32 , 33 ]. With newer methods and database advancements, public health impact through the use of routine genotyping in tuberculosis is increasingly evident [ 4 , 6 , 34 , 35 ]. In conclusion, a combination of strong interjurisdictional networks for data-sharing and regular updates to genotyping methods can maximize the effectiveness of surveillance approaches and programs for infectious diseases.…”
Section: Discussionmentioning
confidence: 99%
“…MTBC members have been documented in > 40 wildlife species, and in 2018 > 150,000 human tuberculosis cases globally were reported to be of zoonotic origin, mostly M. bovis from cattle and ungulates 35 . In 2020, Canada reported a 15-fold increase in the prevalence of tuberculosis (primarily M. tuberculosis Euro-American lineage 4.8) between the Inuit and the general population 36 . This high incidence led the Inuit Tapiriit Kanatami (the representative organization for Inuit in Canada) and the federal government to prioritize the elimination of tuberculosis from Inuit regions by 2030 37 .…”
Section: Introductionmentioning
confidence: 99%